2008
DOI: 10.1186/1471-2164-9-301
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression of the honey bee Apis mellifera associated with Varroa destructor infection

Abstract: Background: The parasitic mite, Varroa destructor, is the most serious pest of the western honey bee, Apis mellifera, and has caused the death of millions of colonies worldwide. This mite reproduces in brood cells and parasitizes immature and adult bees. We investigated whether Varroa infestation induces changes in Apis mellifera gene expression, and whether there are genotypic differences that affect gene expression relevant to the bee's tolerance, as first steps toward unravelling mechanisms of host response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(186 citation statements)
references
References 67 publications
7
173
4
2
Order By: Relevance
“…3c, d). This difference may partially explain the results reported in the literature (Gregory et al, 2005;Navajas et al, 2008;, which could have been due to overlooked health conditions of the experimental populations. Host condition is an important factor that influences the bee response to any environmental challenge and the complex cross-talk between stress and immunity.…”
Section: Varroa Destructor Is a Vector Of Honeybee Viruscontrasting
confidence: 55%
“…3c, d). This difference may partially explain the results reported in the literature (Gregory et al, 2005;Navajas et al, 2008;, which could have been due to overlooked health conditions of the experimental populations. Host condition is an important factor that influences the bee response to any environmental challenge and the complex cross-talk between stress and immunity.…”
Section: Varroa Destructor Is a Vector Of Honeybee Viruscontrasting
confidence: 55%
“…The very close relationship between the mite and the virus, along with the complexity of the results from transcriptomic studies, have generated a somewhat contrasting picture, however. The initially proposed primary role for the parasitic mite in the induction of this immune syndrome (33) has been challenged by several studies that apparently do not support this hypothesis (12,22,(34)(35)(36), even though the possibility that Varroa feeding and its saliva may modulate immune effector molecules cannot be ruled out, as suggested by the effect of this secretion on insect hemocytes in vitro (37). Moreover, a direct immunosuppressive activity of DWV targeting the antiviral barriers under NF-κB control has been proposed in the framework of a bistable dynamic model that assumes a transition from immunostimulation to immunosuppression as the DWV titer increases and then exceeds a critical threshold (Ct) (10).…”
Section: Discussionmentioning
confidence: 99%
“…The mite-susceptible colonies produced almost twice the amount of honey compared to the mite-resistant colonies, and no major differences in swarming tendency were observed (Le Conte et al 2007). Navajas et al (2008) compared gene expression in honeybees of the Avignon mite-resistant population and local mite-susceptible honeybees. Their study interestingly found that several genes involved in olfactory cognition and neuronal excitability were upregulated in the mite-resistant honeybees (Navajas et al 2008).…”
Section: Avignon Francementioning
confidence: 99%
“…Navajas et al (2008) compared gene expression in honeybees of the Avignon mite-resistant population and local mite-susceptible honeybees. Their study interestingly found that several genes involved in olfactory cognition and neuronal excitability were upregulated in the mite-resistant honeybees (Navajas et al 2008). The Avignon miteresistant honeybees could have a higher sensitivity to environmental stimuli and be better adapted for detecting and removing mite-infested brood cells (Navajas et al 2008).…”
Section: Avignon Francementioning
confidence: 99%